STRATEGY TO IMPROVE THE QUALITY OF EDUCATION IN REMOTE AREAS THROUGH A TECHNOLOGICAL APPROACH - Eneng Martini (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research aims to examine various strategies that have been implemented in an effort to improve the quality of education in remote areas through a technological approach. The method used is a literature study by examining various scientific journals, policy reports and other relevant publications published in the last five years. The results of the study show that the use of technology such as online-based learning, the use of digital devices (tablets/laptops), and the development of learning management systems (LMS) have a positive impact on access and quality of education in disadvantaged areas. However, major challenges such as limited infrastructure, lack of training for educators, and lack of policy support remain significant obstacles. Effective strategies include strengthening ICT-based teacher training, collaboration between the government and the private sector in providing infrastructure, and developing a curriculum that is adaptive to the local context. This research recommends an integrative approach that combines technology, human resource training, and sustainable policies to create an inclusive and quality education system in remote areas.